PENGARUH STRUKTUR AKTIVA (ASSETS STRUCTURE), RETURN ON ASSETS DAN PERTUMBUHAN PENJUALAN (GROWTH OF SALES) TERHADAP STRUKTUR MODAL (CAPITAL STRUCTURE) PADA PERUSAHAAN PROPERTY DAN REAL ESTATE DI BURSA EFEK INDONESIA TAHUN 2011 â 2015 - Chandra, Annie; Tantoni, Wenny; Villany, Windy; Lubis, Mahmuddin Syah; Akbar, Faisal (JURNAL RISET AKUNTANSI GOING CONCERN, 2018)
The purpose of the research is to know and analyze the effect of Assets Structure, Return On Assets (ROA) and Growth of Sales on Debt Equity ratio. The research used some theories relating to Assets Structure, Return On Assets, Growth of Sales and Capital Structure. The research approach of this research was quantitative. This type of research is descriptive explanatory. The populations in this research are 53 companies of Property and Real Estate in the Indonesia Stock Exchange in the year of 2011-2015. The result of the research samples were 25 companies of Property and Real Estate in the Indonesia Stock Exchange in the year of 2011-2015. The result of the research as well as a conclusion from this research stated that partially Assets Structure had a negative significant effect on Capital Structure, Partially ROA and Growth of Sales did not have a significant effect on Capital Structure. Simultaneously, Assets Structure, Return On Assets and Growth of Sales had a significant effect on Capital Structure.Keyword: Assets Structure, Return On Assets, Growth of Sales, Debt to Equity Ratio